Komunitas Epifit Berdasarkan Kedalaman Perairan Laut pada Daun Lamun di Pulau Maitara, Provinsi Maluku Utara - Nebuchadnezzar Akbar; Arfa Buamona; Irmalita Tahir; Abdurrachman Baksir; Rustam Effendi; Firdaut Ismail (Jurnal Sumberdaya Akuatik Indopasifik, 2020)
Seagrasses are habitat of various types of sea animals, including association epiphytic in rhizoma, leave and steam. Research about community structure microepiphytic based on depth and ecology index, important as community conditions information. The goal research for ecology index analysis microepiphytic based on depth sea and seagrasses community condition. Sample collections epiphytic on seagrass leave used 1x1 meters quadrant based on depth. Epiphytic sample cutted and scraped in leave surface, than into to bottles sample contain 70% alcohol. The research method used line trasect 50 meters toward sea. The result founded 23 genus epiphytic with biodiversity medium, low dominance and high uniformity.